Gastrointestinal metastases from breast cancer: A case report. (August 2017) - Peinado, Begoña; Álvarez, Estibaliz; Pascual, Isabel; Rubio, Ines; Alvarez, Mario; Luis Marijuan, Jose; Diaz, Joaquin
Abstract : Background: Breast cancer is the most common type of cancer in women nowadays. According to published major studies, the most common sites of metastases of breast cancer are bone, lung, liver and brain. However, it can also metastasize rarely to the gastrointestinal tract. Among the different subtypes of breast cancer, gastrointestinal spread has been associated to infiltrating lobular carcinoma. We present a case of perforated acute diverticulitis that underwent surgery, in which the pathological exam informed of colonic metastasis of lobular breast carcinoma. Case report: A 78-year-old woman, with medical history of high blood pressure, diabetes and left mastectomy performed 14 years ago for infiltrating lobular carcinoma (Stage T2N2M0), with positive estrogenic receptors. Oncological controls showed pleural and bone progression in the last year, so hormonal therapy was indicated. She was admitted to the emergency department due to 72 hours of left lower-quadrant abdominal pain associated with constipation and nausea. On examination she presented tenderness and a palpable mass in the left lower quadrant. Blood tests showed an increased leukocyte count of 13.5x103/µL with neutrophilia, a CRP of 356mg/L and high lactate levels (4.5mmol/L). An abdominal computed tomography (CT) scan showed a left inguinal abscess (6x8x7cm) communicating with an inflammatory mass involving the sigmoid colon, as well as extensive bone metastases, not visualized in previous CTs. An emergency Hartmann's procedure was performed. The postoperative period was uneventful. The pathological report of the surgical specimen informed of infiltration in multiple diverticula by a carcinoma, with morphological pattern and immunohistochemistry compatible with a lobular breast carcinoma. The patient was derived to the Department of Oncology to continue follow-up and hormonal therapy. Conclusions: Gastrointestinal breast metastases are uncommon, however, we should consider this diagnosis in patients with tumoral progression presenting with abdominal symptoms. Metastatic patients should receive medical treatment, reserving surgery for complications like obstruction or perforation, as in the case presented.